Pengaruh Persepsi Wisatawan terhadap Kondisi Kebersihan Lingkungan terhadap Keputusan Berkunjung ke Bali - Nurfadillah Mustari; I Wayan Sugita; Agus Sunatha Putra (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
Environmental cleanliness is one of the important factors in determining the attractiveness of a tourist destination, especially in Bali, which is known as a world-class tourism destination. However, the increasing number of tourist visits has also created challenges in the form of rising waste volume and declining cleanliness quality in several tourist areas. This condition has the potential to influence tourists’ perceptions and their decisions in choosing destinations. This study aims to analyze the influence of tourists’ perceptions of environmental cleanliness on visiting decisions to Bali. The research employed a quantitative approach using a survey method through questionnaires distributed to domestic and international tourists. The data analysis technique used was simple linear regression to examine the relationship between cleanliness perception and visiting decisions. The results showed that tourists’ perceptions of environmental cleanliness have a positive and significant influence on visiting decisions. Tourists tend to choose destinations that are clean, comfortable, and free from waste. These findings confirm that environmental cleanliness is an important element in shaping destination image and increasing tourism competitiveness. Therefore, sustainable efforts from the government, tourism industry stakeholders, and the community are needed to maintain environmental cleanliness to support sustainable tourism in Bali. Environmental cleanliness is one of the important factors in determining the attractiveness of a tourist destination, especially in Bali, which is known as a world-class tourism destination. However, the increasing number of tourist visits has also created challenges in the form of rising waste volume and declining cleanliness quality in several tourist areas. This condition has the potential to influence tourists’ perceptions and their decisions in choosing destinations. This study aims to analyze the influence of tourists’ perceptions of environmental cleanliness on visiting decisions to Bali. The research employed a quantitative approach using a survey method through questionnaires distributed to domestic and international tourists. The data analysis technique used was simple linear regression to examine the relationship between cleanliness perception and visiting decisions. The results showed that tourists’ perceptions of environmental cleanliness have a positive and significant influence on visiting decisions. Tourists tend to choose destinations that are clean, comfortable, and free from waste. These findings confirm that environmental cleanliness is an important element in shaping destination image and increasing tourism competitiveness. Therefore, sustainable efforts from the government, tourism industry stakeholders, and the community are needed to maintain environmental cleanliness to support sustainable tourism in Bali.